The efforts of school counselor to change students’ negative perceptions of guidance and counseling program - Yulistiya Rahmadewi (Program Studi bimbingan Konseling PPs UNM Makassar, 2022)
This study aims to focus on the implementation of counseling guidance in changing students' negative perceptions of counseling guidance, and knowing the facts about the implementation of counseling guidance. Counseling guidance teachers play an important role in the implementation of counseling guidance in schools, through appropriate implementation in making an improvement, generally these negative perceptions can be changed. where the lack of understanding of the role and duties of counseling guidance in schools triggers negative perceptions of the implementation of counseling guidance. Meanwhile, positive perceptions of students can arise if the counseling guidance teacher carries out the task, the role is in line with the code of ethics, and fulfills individual requirements as a teacher. This research uses a qualitative descriptive analysis method, research data is collected through interviews, observations, documentation, where to create results. better counseling guidance work, through increasing competence, professional improvement of counselors, implementing service innovations, using media supporting counseling guidance services, providing input to teachers and schools related to counseling guidance so that they pay more attention to their performance, counseling guidance programs are created and carried out in line with policy , so that students can understand, understand its existence and no longer have a negative perception of counseling guidance.